REGIONAL INTERDEPENDENCE, INDUSTRIALIZATION AND RURAL LAND CONVERSION IN JAVA - HARUN, UTON RUSTAN (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2011)
Global and regional interdependence among ASEAN countries under the open market is leading to unprecedented industrialization and urbanization. The benefit of transnational investment are expected by rural economy and urban systems, as they are becoming more articulated are also benefiting from these investment forces. With market trends, investment activities, and industrialization such rapid change in both urban and rural areas, the theoretical and practical research on urbanization is also undergoing change.In the Bandung Metropolitan Region, which is experiencing rapid urbanization and industrialization, rural areas are being marginalized The phenomena of agricultural persistence in the face of urbanization in the Bandung Metropolitan Area is important to examined so the combination of urban examined and rural activities within this region is explained in the light of desakota development pattern.